Human-Centered Pastoral Governance in the Digital Era: Learning from Sacramental Administration in an Indonesian Catholic Parish - Simon Wenehenubun; Yohanes Langgar Billy; Ferry Doringin (Jurnal Humanipreneur, 2026)
Catholic dioceses across the globe generally face a core governance contradiction: balancing administrative accountability and empathetic pastoral care. Sacrament management is not only a core pillar that maintains the Church’s organizational order, but also shapes believers’ perceptions of the Church’s pastoral mission. This study takes a Catholic diocese in Indonesia as its research subject, adopts an interpretivist qualitative case study method, and recruits interviewees covering clergy, catechists, parish council members, parents, and active parishioners. It collects data through a combination of semi-structured interviews and documentary analysis, to explore the diocese’s stakeholders’ perceptions of pastoral decisions related to sacrament management, as well as the organizational factors that can strengthen community trust. The study finds that stakeholders’ acceptance of pastoral decisions relies far more on five types of relational practices—including compassionate communication, participatory discernment, contextual administrative flexibility, relational accompaniment, and restorative community dialogue—than on administrative outcomes. These practices can foster institutional trust, and turn administrative processes into opportunities for organizational learning. This study originally proposes a people-centered pastoral governance framework with five core dimensions, restructures the governance attributes of sacrament management, and provides a transferable framework for cultivating leadership and community trust for all types of faith-based organizations.